Subtractive genomic approach toward introduction of novel immunogenic targets against Clostridioides difficile: Thinking out of the box. (January 2022) - Noori Goodarzi, Narjes; Fereshteh, Sepideh; Azizi, Omid; Rahimi, Hamzeh; Bolourchi, Negin; Badmasti, Farzad
Abstract: Clostridioides difficile is one of the major causatives of nosocomial infections worldwide. Antibiotic-associated diarrhea, pseudomembranous colitis, and toxic megacolon are the most common forms of C. difficile infection (CDI). Considering the high antibiotic resistance of C. difficile isolates and the low efficacy of immunization with toxin-related vaccines, we suggested that surface-exposed and secreted proteins could be considered as potential immunogenic targets against CDI. Various immuninformatics databases were used to predict antigenicity, allergenicity, B-cell epitopes, MHC-II binding sites, conserved domains, prevalence and conservation of proteins among the most common sequence types, molecular docking, and immunosimulation of immunogenic targets. Finally, 16 proteins belonging to three functional groups were identified, including proteins involved in the cell wall and peptidoglycan layer (nine proteins), flagellar assembly (five proteins), spore germination (one protein), and a protein with unknown function. Molecular docking results showed that among all the mentioned proteins, WP_009892971.1 (Acd) and WP_009890599.1 (a C40 family peptidase) had the strongest interactions with human Toll-like receptor 2 (TLR-2) and TLR-4. This study proposes a combination of C. difficile toxoid (Tcd) and surface-exposed proteins such as Acd as a promising vaccine formulation for protection against circulating clinical strains of C. difficile . Highlights: A reverse vaccinology approach detected putative immunogenic candidates among common sequence types of C. difficile. Sixteen proteins involved in the cell wall, flagella assembly, spore germination, and one hypothetical protein, were characterized. Surface-exposed proteins including WP_009892971.1 (Acd) and WP_009890599.1 (a C40 family peptidase) were excellent immunogenic targets.